(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
This stereotype in the English linguistic culture consists of the following concepts: career, the role of the breadwinner, masculinity, determination, courting women, marriage, fatherhood, friends, entertainment. In the Uzbek language culture, the male stereotype consists of the following concepts: education, work, marriage, family, the role of the breadwinner, responsibility, caring for parents, career advancement, ensuring a future for children, caring for grandchildren.